PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN DASAR-DASAR OTOMOTIF SISWA KELAS X TKRO 1 DI SMK NEGERI 1 KANOR - ARY TEGUH FEBRIYANTO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research is a descriptive research carried out through class action research (Classroom Action Research). The research subjects were students of class X TKRO 1 in the subject of Automotive Fundamentals, material for tools and equipment in the workplace at SMK Negeri 1 Kanor, Bojonegoro Regency. In Cycle I there were 21 students or 58.33% whose study test results were in the Not Passed category, and there were 15 students or 41.67% who were in the Pass category. The average value in Cycle I is 74.31. Based on the learning outcomes of the students in class X TKRO 1, it can be concluded that the first cycle is included in the